(untitled) (Scientific journal of the Fergana State University, 2026)
The aim of this research is to study the functional state of the organism of schoolchildren of different ages and analyze their physiological and psychological characteristics. The study examines factors that influence the functional state of the organism in different age groups of students (primary, middle, and high school), including physical and mental workloads, stress, the learning process, and the social environment. In addition, the psychological state of students, their ability to concentrate and self-regulate, energy expenditure, and recovery processes are thoroughly analyzed. The results of the study show how the functional state of the organism changes depending on the students’ age, as well as how their mental and physical potential develops during the learning process. In this context, the relationship between the students’ overall health, readiness for learning, and their ability to self-manage is identified. The primary significance of the research lies in the development of scientific recommendations for improving the effectiveness of school education and strengthening students’ health, which can be used in pedagogical practice.